(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The demonetization decision was implemented by the government to bring transparency, economy and accountability. The SMEs sector is largely run by contract and daily wage workers. The MSME sector has been hit hard as most mobile workers keep their bank accounts at work. Since the onset of the financial crisis, the MSME s sector is struggling to achieve healthy growth rates and revive the economy. MSME sector faced with huge financial losses due to poor planning of demonetization most closed their units when sales fell. The result demonstrated that the demonetization significantly influence challenges of MSME sector. It is demonstrated that the demonetization significantly influence problems of MSME sector. The research demonstrated that the challenges significantly influence problems of MSME sector. For this, the government should also take initiatives to create awareness about digitization and digitization among illiterate people and in rural areas.